Purification and Characterisation of Bacteriocin Produced by Lactococcus Lactis Subsp. Lactis RW18 Isolated From Steamed Fish (Rastrelliger Sp.) - Lee, Yock Ann (2002)
In this study, eight Lactic Acid Bacteria (LAB) isolated from "Ikan Rebus" (steamed fish) were screened for bacteriocin production using spot-on-lawn, flip streak plate and agar-well diffusion methods. Seven out of eight LAB isolates were confirmed to be able to produce bacteriocin. However, only the highest bacteriocin producer, RW 18, was selected for further studies. The carbohydrate fermentation pattern of RW 18 isolate exhibited 83.4% similarity to Laetoeoeeus laetis subsp. laetis by the API CHL 50 test kit and hence designated as Le. laetis subsp. laetis RW 18. Bacteriocin production by Le. laetis subsp. laetis RW 18 was detected during mid log phase and reached a maximum level of 200 Au/ml during the early stationary phase. Bacteriocin of Le. laetis subsp. laetis RW 18 was able to tolerate wide pH range (pH 3.0 to pH 7.0) but it was unstable when the incubation temperature was increased above 90°C at pH 6.5. The bacteriocin demonstrated a broad-spectrum antagonistic activity against gram-positive bacteria including Listeria monocytogenes, Enterococcus jaecalis, Enterococcus jaecium, Pediococcus acidilactici and Lactobacillus pentosus but it was not active against gram-negative bacteria. Results obtained in the study on the effect of hydrolytic enzymes indicated that the bacteriocin was a proteinaceous compound and most likely to contain lipolytic and glycolytic moieties. The bacteriocin was purified to homogeneity by a procedure involving 0-60% ammonium sulfate precipitation, cation-exchange chromatography and gel filtration chromatography with a yield of 0.9% and purification fold of 3210. The molecular mass of purified bacteriocin was estimated to be 3.9 kDa and 4.0 kDa using the Tricine sodium dodecyl sulphatepolyacrylamide gel electrophoresis (Tricine SDS-PAGE) and gel filtration chromatography respectively. The isoelectric point of the purified bacteriocin was estimated to be more than 9.30 by Isoelectric focusing-PAGE and hence it demonstrated a strong basic (cationic) characteristic. The stability of purified bacteriocin could be improved by adding either BSA or glycerol. A 100% increment of relative activity was obtained by adding 10-40 µg of BSA, whereas a highest relative activity of 300% was achieved when 10% and 15% of glycerol were added respectively. The purified bacteriocins have less antagonistic activity compared to crude bacteriocins. Partially purified bacteriocin pooled from the Resource-S chromatography exhibited enhanced biological activity against LAB, whereas reduced biological activity was observed for purified bacteriocin pooled after superose- 12 gel filtration chromatography. NisA gene was detected in Lc. lactis subsp. lactis RW 18 by PCR amplification using a pair of nisA structural gene specific primers. The RAPD-PCR fingerprinting analysis revealed that Lc. lactis subsp. lac tis RW 18 was genotypically different from nisin producer, Le. lactis subsp. lactis ATCC 11454. Nevertheless, evidence obtained in this study could not prove that the bacteriocin produced by Le. lactis subsp. lactis RW18 was nisin, regardless of the fact that nisA gene was detected in the Le. lactis subsp. lactis RW18. The actual amino acid sequence of the purified bacteriocin has to be determined in order to ascertain whether bacteriocin produced by Le. lactis subsp. lactis RW 18 is nisin.